Tuning of Sm3+ and Er3+-doped TiO2 nanofibers for enhancement of the photocatalytic performance: Optimization of the photodegradation conditions. (15th August 2022) - Pascariu, Petronela; Cojocaru, Corneliu; Homocianu, Mihaela; Samoila, Petrisor
Abstract: Titanium dioxide (TiO2 )-based nanofibers doped with samarium (Sm 3+ ) and erbium (Er 3+ ) at doping levels tuned in the range of 0.05–1.0% were prepared by the electrospinning-calcination method. The produced materials were well characterized by X-ray diffraction, SEM, EDX, and UV–vis diffuse reflectance spectroscopy. These one-dimensional nanostructures showed a crystalline structure with values of fiber diameters values between 60 and 100 nm. The best catalyst sample of this study was formulated as TiO2 :Sm (0.1%) and sintered at 600 °C. And, it was employed to intensify the photocatalytic process under visible-light irradiation. Likewise, the chemometric approach was applied to optimize the process. The results revealed that the rate constant for the photo-degradation of a cationic organic pollutant was significantly improved ( k = 3.496 × 10 −1 min −1 ). In terms of the reaction half-life, the intensification and optimization of the process led to a decrease in the half-life of the reaction from 68 to 2 min. And, these are outstanding findings for the photo-degradation process under visible-light irradiation. In addition, the total organic carbon (TOC) removal efficiencies were found to be 69.95% and 72.30% for the mineralization of MB and CIP, respectively, after a 360 min reaction time, which are significant results. Moreover, this material demonstrated remarkable photocatalytic activity for the degradation of ciprofloxacin (CIP) with a 99.6% removal efficiency and a rate constant of 4.292 × 10 −1 min −1 . Finally, the stability and reusability of this catalyst were demonstrated during five repetitive cycles of the CIP photodegradation. Graphical abstract: Image 1 Highlights: Sm 3+, Er 3+ :TiO2 nanostructured materials were prepared by electrospinning method. The dopants effectively inhibited the growth of crystallites and reduced the E g . The developed nanostructures have enhanced the photocatalytic activity under visible irradiation. The process intensification led to a decrease in the half-life from 68 to 2 min. TOC removal efficiency was found to be 69.95% and 72.30% for the mineralization of MB and CIP.